The Transition to Telehealth: A Pilot Model in a New York City Student-Run Free Clinic During the COVID-19 Pandemic - Brittany Glassberg; Kevin Weiss; Terence Hughes; James Meyers; Samir Kamat; Jonathan Pan; James Blum; James Carter; Cynthia Luo; Samuel Powell; Hannah Krystal; David Thomas; et al. (Journal of Student-Run Clinics, 2021)
Here we describe the development and implementation of a telehealth model for vulnerable, uninsured residents of East Harlem in New York City during the coronavirus disease 2019 (COVID-19) pandemic at a student-run, physician-supervised free clinic. The East Harlem Health Outreach Partnership completed 43 primary care follow-up and 78 urgent telehealth encounters during a six-week trial period during the COVID-19 outbreak, and 40 patients were managed for either suspected or confirmed COVID-19 diagnoses. Telehealth is a useful tool to provide rapid, high-quality care to a large patient population during a pandemic. Challenges include the lack of access to updated technology among patients of lower socioeconomic status and rapidly evolving management guidelines for COVID-19. Telehealth is essential for supporting vulnerable populations during times of reduced physical contact, including the COVID-19 pandemic, but can be applied broadly to all free clinics to augment access.